2017
DOI: 10.1111/febs.14304
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for high‐affinity adipate binding to AdpC (RPA4515), an orphan periplasmic‐binding protein from the tripartite tricarboxylate transporter (TTT) family in Rhodopseudomonas palustris

Abstract: Protein structure co-ordinates are available in the PDB under the accession numbers 5OEI and 5OKU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 61 publications
3
24
0
Order By: Relevance
“…In particular, previous studies showed that the TTT system was present in high quantities in the Amazon River, and this was attributed to a potential degradation of allochthonous organic matter [15]. Recent findings also suggest a TTT system related to the transport of TeOM degradation byproducts [46,47]. Little is known about these transporters, but our findings indicate that TTT is an abundant protein family in the Amazon River, suggesting that tricarboxylates are a common carbon source for prokaryotes in these waters.…”
Section: Discussionsupporting
confidence: 47%
“…In particular, previous studies showed that the TTT system was present in high quantities in the Amazon River, and this was attributed to a potential degradation of allochthonous organic matter [15]. Recent findings also suggest a TTT system related to the transport of TeOM degradation byproducts [46,47]. Little is known about these transporters, but our findings indicate that TTT is an abundant protein family in the Amazon River, suggesting that tricarboxylates are a common carbon source for prokaryotes in these waters.…”
Section: Discussionsupporting
confidence: 47%
“…In particular, previous studies showed that the TTT system was present in high quantities in the Amazon River, and this was attributed to a potential degradation of allochthonous organic matter [38]. Recent findings also suggest a TTT system related to the transport of TeOM degradation byproducts [39,40]. Little is known about these transporters, but our findings indicate that TTT is an abundant protein family in the Amazon River, suggesting that tricarboxylates are a common carbon source for prokaryotes in these waters.…”
Section: Discussionsupporting
confidence: 47%
“…Similarly to the fate of hemi-/cellulose degradation byproducts, lignin degradation ends up in the production of 4-carboxy-4hydroxy-2-oxoadipate, which is converted into pyruvate or oxaloacetate, both substrates of the tricarboxylic acid cycle (TCA) [36]. Recently, several substrate binding proteins (TctC) belonging to the tripartite tricarboxylate transporter (TTT) system were associated to the transport of TeOM degradation byproducts, like adipate [39] and terephthalate [40]. To investigate the metabolism of these compounds, and the possible link between the TTT system and lignin/cellulose degradation, the protein families TctA (PF01970), TctB (PF07331) and TctC (PF03401)…”
Section: Teom Degradation Machinerymentioning
confidence: 99%
“…In particular, previous studies showed that the TTT system was present in high quantities in the Amazon River, and this was attributed to a potential degradation of allochthonous organic matter [14]. Recent ndings also suggest a TTT system related to the transport of TeOM degradation byproducts [46,47]. Little is known about these transporters, but our ndings indicate that TTT is an abundant protein family in the Amazon River, suggesting that tricarboxylates are a common carbon source for prokaryotes in these waters.…”
Section: Discussionmentioning
confidence: 46%
“…Similarly to the fate of hemi-/cellulose degradation byproducts, lignin degradation ends up in the production of 4-carboxy-4hydroxy-2-oxoadipate, which is converted into pyruvate or oxaloacetate, both substrates of the tricarboxylic acid cycle (TCA) [44]. Recently, several substrate binding proteins (TctC) belonging to the tripartite tricarboxylate transporter (TTT) system were associated with the transport of TeOM degradation byproducts, like adipate [46] and terephthalate [47]. To investigate the metabolism of these compounds, and the possible link between the TTT system and lignin/cellulose degradation, the protein families TctA (PF01970), TctB (PF07331) and TctC (PF03401) were searched in PFAM.…”
Section: Potential Teom Degradation Machinerymentioning
confidence: 99%